2021
DOI: 10.1186/s40494-021-00605-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of the vegetation carbon storage in the sanjiang plain to changes in land use/cover and climate

Abstract: Large-scale human activities especially the destruction of forest land, grassland, and unused land result in a large amount of carbon release into the atmosphere and cause drastic changes in land use/cover in the Sanjiang Plain. As a climate change-sensitive and ecologically vulnerable area, the Sanjiang Plain ecosystem’s carbon cycle is affected by significant climate change. Therefore, it is important that studying the impact of the changes in land use/cover and climate on vegetation carbon storage in the Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The marsh on the Sanjiang Plain plays a crucial role in regional biodiversity conservation and the carbon cycle (Sui et al, 2019 ). Some studies have analyzed the variations in marsh AGB and the effects of climatic change on marsh AGB in the Sanjiang Plain (Shi et al, 2015 ; Li et al, 2021 ). For example, Ni et al ( 1996 ) studied the influences of hydrothermal conditions and the AGB of Deyeuxia angustifolia in the Sanjiang Plain marshes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marsh on the Sanjiang Plain plays a crucial role in regional biodiversity conservation and the carbon cycle (Sui et al, 2019 ). Some studies have analyzed the variations in marsh AGB and the effects of climatic change on marsh AGB in the Sanjiang Plain (Shi et al, 2015 ; Li et al, 2021 ). For example, Ni et al ( 1996 ) studied the influences of hydrothermal conditions and the AGB of Deyeuxia angustifolia in the Sanjiang Plain marshes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ni et al ( 1996 ) studied the influences of hydrothermal conditions and the AGB of Deyeuxia angustifolia in the Sanjiang Plain marshes. Shi et al ( 2015 ) analyzed the effects of different water levels on the AGB of vegetation in the freshwater marshes of the Sanjiang Plain and found that increasing water levels promoted the biomass of D. angustifoli a. Li et al ( 2021 ) analyzed the influences of temperature and precipitation on AGB and found that the increase of precipitation can increase the AGB in the Sanjiang Plain. However, these studies focused on analyzing changes in marsh AGB and their responses to climatic change at a species scale, and no research has been conducted over the entire Sanjiang Plain due to the limitations of field investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Mountainous vegetation is rich and diverse, and improving the estimation accuracy of the ecological carbon sequestration in mountainous areas can provide a clearer understanding of the ecological carbon sequestration capacity of mountain vegetation (Xu et al, 2020;Jiang et al, 2021;Li H. et al, 2021;Zhang et al, 2021). Wang et al (2020) showed that from 2010 to 2016 in mainland China, the carbon sequestration of terrestrial ecosystems was 45% of the anthropogenic carbon emissions during the same period, approximately 1.11 billion tons, and these carbon sequestration contributions are mainly due to the strong ecological carbon sequestration capacity in the southwestern mountainous areas of China.…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, Geng et al revised the CASA model's parameters based on the Digital Elevation Model (DEM) data to increase the estimation accuracy of the CASA (Wang H. et al, 2019;Wang Y. et al, 2019), but this method's correcting effect on terrain falling shadow is subpar. Early studies have shown (Sun et al, 2016;Li H. et al, 2021) that changing model parameters is challenging when assessing vegetation carbon sequestration at a wide range of regional scales. They only established the value range of ε max based on experimental data but did not establish a functional relation between terrain parameters and the ε max (Han, 2020;Peng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, natural heritage sites and biosphere reserves are recognized as sensitive areas for climate change and ecological degradation. In Li et al [ 9 ], the dynamic response of the vegetation carbon storage to the land use/cover was assessed by synergistically using remote sensing images and temperature and precipitation data in the Sanjiang Plain in China. Apart from the visible environmental changes, the imperceptible deformations for the decline of architectural heritages were monitored in Xu et al using multi-temporal synthetic aperture interferometry (MTInSAR) approaches taking advantage of the capability in estimating spatiotemporal deformations with accuracy up to millimeters, as verified by the comparative case study of the Shanhaiguan section of the Great Wall (China) [ 10 ].…”
mentioning
confidence: 99%